2014
DOI: 10.1021/tx500142f
|View full text |Cite
|
Sign up to set email alerts
|

Reference Particles for Toxicological Studies of Wood Combustion: Formation, Characteristics, and Toxicity Compared to Those of Real Wood Combustion Particulate Mass

Abstract: Multiple studies show that particulate mass (PM) generated from incomplete wood combustion may induce adverse health issues in humans. Previous findings have shown that also the PM from efficient wood combustion may induce enhanced production of reactive oxygen species (ROS), inflammation, and cytotoxicity in vitro and in vivo. Underlying factors of these effects may be traced back to volatile inorganic transition metals, especially zinc, which can be enriched in the ultrafine fraction of biomass combustion pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…The simultaneous dilution and cooling quenched the reactions, prevented re-condensation of the solvent and decreased the wall deposition losses of the produced particles. Furthermore, FSP-1 (ZnO rods) were previously produced with flame spray pyrolysis as described in detail by Torvela et al 2014.…”
Section: Materials For Nanoparticle Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…The simultaneous dilution and cooling quenched the reactions, prevented re-condensation of the solvent and decreased the wall deposition losses of the produced particles. Furthermore, FSP-1 (ZnO rods) were previously produced with flame spray pyrolysis as described in detail by Torvela et al 2014.…”
Section: Materials For Nanoparticle Synthesismentioning
confidence: 99%
“…The particle size distribution was determined using a scanning mobility particle sizer (SMPS, DMA 3081 with CPC 3775, TSI Inc.) and number concentration was measured using a condensation particle counter (CPC 3775,TSI Inc.). The properties of FSP generated particles were measured with the fast mobility particle sizer (FMPS 3091, TSI Inc.) (Torvela et al, 2014). The concentrations determined with the FMPS and SMPS were corrected with the dilution ratios.…”
Section: Particle On-line and Off-line Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…While the trends in specic activity as a function of particle size at the urban background (15.5, 12.5, 4) and rural (14, 7.5, 5) (PM 3 , PM 7-3 , PM >7 respectively) sites are very similar to that observed with the ROS data (consistent decrease with increasing particle size), the trend is dramatically different at the canyon sites with median PM 7-3 activity of 20.5 compared with 7.5 in the PM 3 and 7 in the PM >7 . The canyon sites/cities contributing most signicantly to this "elevated" PM 7-3 specic activity were Stockholm (25)(26)(27)(28)(29)(30), Frankfurt (22) and Thessaloniki (20.5). The highest PM 3 specic activities were measured at urban background sites in Frankfurt (27), Stockholm (18) and London (17) (Fig.…”
Section: Particle Size-resolved Analysismentioning
confidence: 99%
“…Multiple studies have demonstrated various macrophage cell lines to respond to PM exposure with a release of pro-inam-matory signals. [25][26][27][28][29] Recent studies reported that PM-derived water-soluble transition metals (e.g. Fe, Ni, Cu, Cr, Mn, Zn and V) correlate signicantly with the oxidative potential of airborne PM across different urban areas and size ranges.…”
Section: Introductionmentioning
confidence: 99%